2016
DOI: 10.1111/jrh.12187
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Financial Distress and Closure in Rural Hospitals

Abstract: This methodology offers improved specificity and predictive power relative to existing measures of financial distress applied to rural hospitals. This risk assessment tool may inform programs at the federal, state, and local levels that provide funding or support to rural hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 35 publications
1
72
0
Order By: Relevance
“…PCFs with larger PCDGS did provide more comprehensive preventive and public health services but paid a price of reduced basic medical care services due to decreased financial revenue by the current pricing regulation and ceiling line set by the medical insurance system [16,17]. This is consistent with the fact that services provided across the United States Critical Access Hospitals are associated with the portion of charges and cost received from Medicare payment [44]. As the primary care system with comprehensive care demonstrated better health outcomes [45,46], future reform of the DGS system should establish an evaluation system that incentivizes wider provision of primary care services [47].…”
Section: Discussionmentioning
confidence: 59%
“…PCFs with larger PCDGS did provide more comprehensive preventive and public health services but paid a price of reduced basic medical care services due to decreased financial revenue by the current pricing regulation and ceiling line set by the medical insurance system [16,17]. This is consistent with the fact that services provided across the United States Critical Access Hospitals are associated with the portion of charges and cost received from Medicare payment [44]. As the primary care system with comprehensive care demonstrated better health outcomes [45,46], future reform of the DGS system should establish an evaluation system that incentivizes wider provision of primary care services [47].…”
Section: Discussionmentioning
confidence: 59%
“…Consideration of these hospital and market characteristics is particularly important given the growing number of rural hospitals at risk of financial distress 11 and closure. 5 Rural hospitals with greater odds of financial distress share similar hospital and market characteristics with the hospitals that would be most negatively affected by loss of the ACA LVH adjustment: they are more likely to be smaller hospitals, located in smaller communities, 11 located in the South, 12 and located in communities with higher poverty rates.…”
Section: Discussionmentioning
confidence: 99%
“…5 Rural hospitals with greater odds of financial distress share similar hospital and market characteristics with the hospitals that would be most negatively affected by loss of the ACA LVH adjustment: they are more likely to be smaller hospitals, located in smaller communities, 11 located in the South, 12 and located in communities with higher poverty rates. 11 Similarly, research by Thomas and colleagues 13 found that, compared to rural hospitals in financial distress that remained open during the same period, closed rural hospitals were more likely to be located in markets with higher percentages of black and Hispanic/Latino residents and with higher rates of unemployment. 13 Given the similarities between the hospitals and hospital markets that would be most affected by loss of the ACA LVH adjustment and the rural hospitals at risk of financial distress and closure, policy makers might want to consider the risk of financial distress and closure when deciding whether to modify the existing ACA LVH program.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the following financial indicators are employed: (1) Profitability, (2) liquidity, (3) capital structure, (4) revenue indicators, (5) costs, and (6) utilization (bed occupancy) [57,68,69]. Most of the previous studies confirm rural hospitals' poor financial performance (based on indicators listed above) [37,69,70], while some results are inconsistent, suggesting that rural hospitals can be as profitable (or efficient) as their urban counterparts [58,71]. According to the pillars of the environment of the traditional definition of sustainable development, the efficiency of rural hospitals can help them use their resources in the best way and to direct them toward their missions of patient care.…”
Section: Rural Hospitals As Part Of a Sustainable Health Systemmentioning
confidence: 99%